g-1(7)=3

Divide each term in g-1(7)=3 by 7.

g-1(7)7=37

Simplify g-1(7)7.

Move g-1 to the denominator using the negative exponent rule b-n=1bn.

77g=37

Cancel the common factor of 7.

Cancel the common factor.

77g=37

Rewrite the expression.

1g=37

1g=37

1g=37

1g=37

Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.

1⋅7=g⋅3

Rewrite the equation as g⋅3=1⋅7.

g⋅3=1⋅7

Multiply 7 by 1.

g⋅3=7

Divide each term by 3 and simplify.

Divide each term in g⋅3=7 by 3.

g⋅33=73

Cancel the common factor of 3.

Cancel the common factor.

g⋅33=73

Divide g by 1.

g=73

g=73

g=73

g=73

The result can be shown in multiple forms.

Exact Form:

g=73

Decimal Form:

g=2.3‾

Mixed Number Form:

g=213

Solve for g g^-1(7)=3